2005
DOI: 10.1093/jn/135.2.218
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Vitamin D Deficiency Is Increased in Adolescent Girls Who Wear Concealing Clothing

Abstract: Vitamin D deficiency continues to be a worldwide problem, especially in developing countries. The aim of this study was to investigate potential risk factors for vitamin D deficiency. Girls (n = 89) aged 13 to 17 y were enrolled in the study. Study subjects were stratified into 3 groups: Group I included girls living in a suburban area; Group II girls lived in an urban area, and Group III girls lived in an urban area and wore concealing clothes for religious reasons. At the end of winter (in April) serum 25-hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
98
10
9

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(126 citation statements)
references
References 34 publications
9
98
10
9
Order By: Relevance
“…[24] Findings of the current study have shown that vitamin D was significantly low in obese children compare to control children. These findings are consistent with the previous study of Hatun S et al, [8] Kadowaki S et al and Lee S ea al in which they observed a siginificant decrease of vitamin D in obese children compare to non-obese children. [9,10] Similarly, Scragg R et al, 11 Holick MF et al, [12] and Reis AF et al, [13] recorded significantly low vitamin D in comparison of higher BMI.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…[24] Findings of the current study have shown that vitamin D was significantly low in obese children compare to control children. These findings are consistent with the previous study of Hatun S et al, [8] Kadowaki S et al and Lee S ea al in which they observed a siginificant decrease of vitamin D in obese children compare to non-obese children. [9,10] Similarly, Scragg R et al, 11 Holick MF et al, [12] and Reis AF et al, [13] recorded significantly low vitamin D in comparison of higher BMI.…”
Section: Discussionsupporting
confidence: 93%
“…Various studies suggested that decrease vitamin D level is increased insulin resistance in adults. [8][9][10][11] Findings of the present study show that insulin resistance was significantly higher in obese children compare to healthy children. However, there was an insignificant difference of HOMA-IR in comparison of deficient, insufficient and sufficient level of vitamin D in obese children.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…In studies of Middle Eastern groups, females have been reported to have significantly lower 25(OH)D levels. [41][42][43] This has been attributed to required clothing covering all skin and thereby reducing exposure to UVB. 44 In South Africa, the Mediterranean and other sun-rich areas the relevance of this study may not be immediately apparent.…”
Section: Discussionmentioning
confidence: 99%
“…Despite high sunlight hours, vitamin D deficiency is well described in women in the Middle East, primarily as a result of cultural norms of keeping skin covered (22,23) . With the majority of vitamin D studies in the Middle East focusing on women (15,(22)(23)(24) , young men appear to be an under-recognized at-risk group (15,25) . Indeed, in the 1980s, 73 % of young Saudi Arabian men were found to have 25(OH)D levels less than 10 ng/ml (26) .…”
mentioning
confidence: 99%